MASLOW’S HIERARCHY OF HUMAN NEEDS OF THE MAIN CHARACTER IN ABRAHAM LINCOLN VAMPIRE HUNTER FILM (2012) - Nurlela, Nurlela; Natsir, M.; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
People have different dream in their life. To fulfill the dream, they need motivation because it makes people stronger to achieve their dream. The researcher identified the motivation hierarchy of human needs of the main character in Abraham Lincoln Vampire Hunter film using Maslow’s theory. Abraham’s character is basically motivated by his revenge to fulfill his human needs. This study discussed about the human needs of Abraham Lincoln as the main character in the film. This study was a descriptive qualitative study. The primary data were presented in the form of dialogues throughout the movie related to human needs of Abraham’s character in Abraham Lincoln Vampire Hunter film. The secondary data were supported by the previous studies, journals, theories and books. The data source was taken from the script, and dialogue of Abraham Lincoln Vampire Hunter film. The result of this study showed that the researcher finds that Abraham’s character in Abraham Lincoln Vampire Hunter film fulfilled all of five stages of the hierarchy of human needs by Abraham Maslow such as physiological needs, the belongingness, esteem needs, safety needs. But he struggles to fulfil his self-actualization needs because to achieved his dream, he needs to do some works such as hunting the vampires.